Relationship of Echocardiographic Z Scores Adjusted for Body Surface Area to Age, Sex, Race, and Ethnicity: The Pediatric Heart Network Normal Echocardiogram Database. (November 2017) - Lopez, Leo; Colan, Steven; Stylianou, Mario; Granger, Suzanne; Trachtenberg, Felicia; Frommelt, Peter; Pearson, Gail; Camarda, Joseph; Cnota, James; Cohen, Meryl; Dragulescu, Andreea; Frommelt, Michele; et al.
Abstract : Background—: Published nomograms of pediatric echocardiographic measurements are limited by insufficient sample size to assess the effects of age, sex, race, and ethnicity. Variable methodologies have resulted in a wide range of Z scores for a single measurement. This multicenter study sought to determine Z scores for common measurements adjusted for body surface area (BSA) and stratified by age, sex, race, and ethnicity. Methods and Results—: Data collected from healthy nonobese children ⩽18 years of age at 19 centers with a normal echocardiogram included age, sex, race, ethnicity, height, weight, echocardiographic images, and measurements performed at the Core Laboratory. Z score models involved indexed parameters (X/BSA α ) that were normally distributed without residual dependence on BSA. The models were tested for the effects of age, sex, race, and ethnicity. Raw measurements from models with and without these effects were compared, and <5% difference was considered clinically insignificant because interobserver variability for echocardiographic measurements are reported as ≥5% difference. Of the 3566 subjects, 90% had measurable images. Appropriate BSA transformations (BSA α ) were selected for each measurement. Multivariable regression revealed statistically significant effects by age, sex, race, and ethnicity for all outcomes, but all effects were clinically insignificant based on comparisons of models with and without the effects, resulting in Z scores independent of age, sex, race, and ethnicity for each measurement. Conclusions—: Echocardiographic Z scores based on BSA were derived from a large, diverse, and healthy North American population. Age, sex, race, and ethnicity have small effects on the Z scores that are statistically significant but not clinically important. Abstract : Supplemental Digital Content is available in the text.